DETERMINATION OF HOMOGENEITY OF FEED FOR ANIMALS USING FERROMAGNETIC MICROTRACERS - Sakhno, T. V.; Semenov, A. O.; Sakhno, Y. E.; Barashkov, N. N. (Scientific Progress & Innovations, 2022)
As the productivity of animals increases, there is a necessity to increase the requirements for feed homogeneity. In countries with developed livestock feed with homogeneity of 95 % consider to be excellent, 90 % – good, 80 % or less – unacceptable. The requirement for homogeneity of compound feeds has increased in recent years due to the complexity of their formulation, which includes more and more components. Besides, it is not important whether the components get into the feed directly through the mixer or they introduced through premixes. The article substantiates the feasibility of using ferromagnetic microtracers to evaluate the homogeneity of feed in order to improve their quality, and obtain an international certificate of GMP + (B1 and B2). Ferromagnetic microtracers are particles of iron or stainless steel, on the surface of which are adsorbed food dyes of different colors. When preparing vitamin, mineral or medicinal premixes, the microtracer is used to indicate their presence in the finished feed, as well as to identify feed additives and feeds containing such additives. The studies were performed using a rotary detector using manufacturer-certified Microtracers F-series (particle size from 125 to 400 microns). Analysis of the quality of the mixing process was performed in accordance with the new version of the GMP + BA2 standard using as an example a domestic feed mill. 20 samples were taken and statistical evaluation was performed according to the Poisson distribution. The calculated probability of homogeneity of compound feed mixing was good (p = 5.1 %), which meets the requirements of the international standard GMP + B1. Such feed is safe for animals and provides guarantees to the consumer in the production, processing, trade, storage and transportation of feed ingredients and animal feed not only in Ukraine but also in most European countries.